2011
DOI: 10.1108/09699981111180917
|View full text |Cite
|
Sign up to set email alerts
|

Risk matrix for factors affecting time delay in road construction projects: owners' perspective

Abstract: PurposeThe aim of this study is to identify the risk matrix for factors causing time delay in road construction projects in the West Bank in Palestine from owners' viewpoint.Design/methodology/approachIn total, 43 factors that might cause delays of road construction projects were defined through a detailed literature review. The factors were tabulated in a questionnaire form, which was sent out to a total of 25 public owners asking their contribution in identifying the risk matrix for the 43 factors in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 11 publications
(12 reference statements)
2
62
0
1
Order By: Relevance
“…Thus, this result illustrates the importance of rising awareness among the contracting parties to ensure a culture of team work and to achieve their desires of a less adversarial working climate. This result is supported by several of the investigated studies (Mahamid, 2011;Alghbari et al, 2007;Sambasivan and Soon, 2007).…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Thus, this result illustrates the importance of rising awareness among the contracting parties to ensure a culture of team work and to achieve their desires of a less adversarial working climate. This result is supported by several of the investigated studies (Mahamid, 2011;Alghbari et al, 2007;Sambasivan and Soon, 2007).…”
supporting
confidence: 75%
“…In a survey of the West Bank in Palestine, Mahamid (2011) indicated that the most severe factors affecting time delay in road construction projects from the owners' perspective are: poor communication between construction parties, poor resource management, delays in commencement, insufficient inspectors, and rework. Similarly, Al-Najjar (2008) concluded that the most important factors causing time overruns in building construction projects in the Gaza Strip as perceived by contractors were: strikes, Israeli attacks and border closures, lack of materials in the markets, shortage of construction materials at site, delays of material deliveries to site, cash shortages during construction, poor site management, poor economic conditions (currency, inflation rate, etc), shortage of equipment and tools on site, and owner delay in freeing the contractors payments for completed work.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Mahamid (2011) indicated that the most severe factors affecting time delay in road construction projects in the West Bank in Palestine from the owner perspective are: poor communication between construction parties, poor resource management, delay in commencement, insufficient inspectors, and rework. Al-Najjar (2008) concluded that the top affecting factors that cause time overrun in building construction projects in Gaza Strip as perceived by contractors are: strikes, Israeli attacks and border closures, lack of materials in markets, shortage of construction materials at site, delay of material delivery to site, cash problem during construction, poor site management, poor economic conditions (currency, inflation rate, etc), shortage of equipment at site, equipments and tool shortage on site, and owner delay in freeing the contractor financial payments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study recommends to construction industry bodies to take the benefit of homogeneity of the research in developing and implementing strategies for improvement and innovation in training programs related to project management. Another research by Mahamid [10] aimed to identify the risk matrix for factors affecting delays in road construction projects in the West Bank in Palestine from the owners' perspective. The results identified eight severe factors that are located in the red zone which are: poor communication between construction parties; poor resource management; delay in commencement; insufficient inspectors; rework from poor material quality; rework from poor workmanship; payments delay; and segmentation of the West Bank…”
Section: Introductionmentioning
confidence: 99%